Analysis of CSR Ecological Knowledge and Conservation Behavior Relationships Among Serang Beach Coastal Local Communities - Muhamad Zakaa Choirul Mustofa; Rizka Hadya (SENTRI: Jurnal Riset Ilmiah, 2025)
The marine ecosystem in Serang Beach faces serious threats caused by low public awareness of conserving protected sea turtle species, including green turtles, loggerhead turtles, and hawksbill turtles. This study aims to analyze the relationships between Corporate Social Responsibility (CSR) programs, ecological knowledge, and community conservation behavior, while emphasizing CSR’s role in human resource management as a contributor to capacity building among coastal communities in Serang Beach, Blitar Regency. This quantitative correlational research involved 46 purposively selected respondents. Data on ecological knowledge and conservation behavior were collected through questionnaires and analyzed using the Spearman rank correlation test. The results showed significance values of 0.000 < 0.05 for the relationships between CSR and ecological knowledge, CSR and conservation behavior, and ecological knowledge and conservation behavior. These findings indicate significant positive correlations among the variables. The study concludes that CSR programs play an important role in improving ecological knowledge and shaping pro-environmental behavior. Increased ecological knowledge also reinforces community participation in turtle conservation efforts. Overall, the research highlights the importance of strengthening CSR initiatives as sustainable strategies for empowering coastal communities and supporting long-term marine conservation. Strengthening these programs can encourage better collaboration between local stakeholders, enhance environmental stewardship, and foster more resilient community practices. The study also suggests that consistent CSR engagement can help build a culture of conservation, ensuring that community members develop the skills, motivation, and awareness necessary to protect endangered species. Such efforts contribute to broader ecological sustainability and support regional conservation priorities in the study area today.